Social Cognitive Domain Coordination in Left-Behind Children: A Comparative Study of Left-Behind and Non-Left-Behind Children in Rural China - Liu, Jianjin (ETHICS IN PROGRESS, 2016)
Forty-seven left-behind children (LB) and 40 non-left-behind children (NL) in rural China were interviewed to evaluate moral, conventional, and personal violations by providing judgments and justifications. The results suggested that both LBs and NLs differentiate the rules of moral, conventional and personal domains. However, there are some differences: 1. The NL considered it acceptable to commit a personal infraction when there was no rue prohibiting it, while the LB considered it wrong; 2. The younger male LBs were more willing to accept situations without moral psychological rules, compared with younger female LBs, older male LBs, and younger male NLs. Age, sex differences were also found. The one out of our expectation is that younger males considered it more acceptable to commit a personal infraction than older males did and believed it all right if there was no explicit rule on it. Meanwhile, in providing reasons to support their judgments or evaluations, the findings revealed that: 1. More often LBs referred to social conventional reasoning even when evaluating moral and personal rules and violations, especially on personal issues; 2. LBs used more justifications of punishment and fewer justifications of personal growth. The implications of the results of the study for children’s moral development and education, especially for LBs, are discussed.